Analisis Daya Mobil Listrik Terhadap Intensitas Cahaya - Mukhamad Khumaidi Usman; Amin Nur Akhmadi (Fakultas Teknik UMSU, 2021)
The body's electrical system has a very important role in a vehicle, namely as the main lighting during night trips as well as a signal to signal other drivers when turning and braking as well as the sound of the horn as an element of safety in a complete vehicle. Problems that often occur in the electrical system of the body, especially in the electrical system of the headlamps or headlights, use incandescent lamps, have very large power so that they are less efficient in terms of energy savings, using LED lamps can cut the current used. The test results show that the LED lamp is indeed more efficient in terms of current to be used as the electrical system for the headlight body, and has a higher light intensity than incandescent lamps. The light intensity produced by the bulb with a current requirement of 1.86 Ampere 1073.9 Lux, for halogen lamps with a current requirement of 2.45 Ampere 2213.97 Lux, while for the LED lamp is 0.47 Ampere 1150 Lux. Of the nine lamp brands tested, the Osram LED lamp is a very good lamp, because it only requires a current of 0.44 Ampere to produce a light intensity of 2200.2 Lux.